Mutations of the histone linker H1–4 in neurodevelopmental disorders and functional characterization of neurons expressing C-terminus frameshift mutant H1.4. Issue 9 (12th November 2021) - Tremblay, Martine W; Green, Matthew V; Goldstein, Benjamin M; Aldridge, Andrew I; Rosenfeld, Jill A; Streff, Haley; Tan, Wendy D; Craigen, William; Bekheirnia, Nasim; Al Tala, Saeed; West, Anne E; Jiang, Yong-hui
Abstract: Rahman syndrome (RMNS) is a rare genetic disorder characterized by mild to severe intellectual disability, hypotonia, anxiety, autism spectrum disorder, vision problems, bone abnormalities and dysmorphic facies. RMNS is caused by de novo heterozygous mutations in the histone linker gene H1–4 ; however, mechanisms underlying impaired neurodevelopment in RMNS are not understood. All reported mutations associated with RMNS in H1–4 are small insertions or deletions that create a shared frameshift, resulting in a H1.4 protein that is both truncated and possessing an abnormal C -terminus f rameshifted t ail (H1.4 CFT). To expand understanding of mutations and phenotypes associated with mutant H1–4, we identified new variants at both the C- and N-terminus of H1.4. The clinical features of mutations identified at the C-terminus are consistent with other reports and strengthen the support of pathogenicity of H1.4 CFT. To understand how H1.4 CFT may disrupt brain function, we exogenously expressed wild-type or H1.4 CFT protein in rat hippocampal neurons and assessed neuronal structure and function. Genome-wide transcriptome analysis revealed 400 genes altered in the presence of H1.4 CFT. Neuronal genes downregulated by H1.4 CFT were enriched for functional categories involved in synaptic communication and neuropeptide signaling. Neurons expressing H1.4 CFT also showed reduced neuronal activity on multielectrode arrays. These data are the first to characterize the transcriptional and functional consequence of H1.4 CFT in neurons. Our data provide insight into causes of neurodevelopmental impairments associated with frameshift mutations in the C-terminus of H1.4 and highlight the need for future studies on the function of histone H1.4 in neurons.